2014
DOI: 10.1080/08997659.2013.860060
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the VP2 Gene of Infectious Pancreatic Necrosis Virus (IPNV) Isolates from Mexico

Abstract: Infectious pancreatic necrosis virus (IPNV) is one of the most important viruses in the Pacific salmon Oncorhynchus spp., Atlantic Salmon Salmo salar, and Rainbow Trout O. mykiss industry. This virus has been shown to produce high mortality among salmonid fry and juveniles, and survivors might become carriers. Since 2000, IPNV has affected Mexican Rainbow Trout culture, resulting in considerable economic losses. In the current study, molecular characterization of the VP2 gene of a number of Mexican IPNV isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
1
10
0
3
Order By: Relevance
“…The fish came from farms displaying IPN‐like disease outbreaks, histopathological lesions were in line with that of IPN, however, bacterial co‐infections could have contributed, and thus clinical signs and mortality cannot solely be ascribed to IPN. Nevertheless, similar sequence observations have also been found in other recent studies, where isolates responsible for IPN outbreaks harbour the so‐called low to non‐virulent motif (Eriksson‐Kallio et al., ; Ruane, Mccarthy, Swords, & Henshilwood, ; Salgado‐Miranda, Rojas‐Anaya, Garcia‐Espinosa, & Loza‐Rubio, ). Whether this represents species‐specific virulence motifs of IPNV, that is, Atlantic salmon versus rainbow trout, can only be speculated.…”
Section: Discussionsupporting
confidence: 86%
“…The fish came from farms displaying IPN‐like disease outbreaks, histopathological lesions were in line with that of IPN, however, bacterial co‐infections could have contributed, and thus clinical signs and mortality cannot solely be ascribed to IPN. Nevertheless, similar sequence observations have also been found in other recent studies, where isolates responsible for IPN outbreaks harbour the so‐called low to non‐virulent motif (Eriksson‐Kallio et al., ; Ruane, Mccarthy, Swords, & Henshilwood, ; Salgado‐Miranda, Rojas‐Anaya, Garcia‐Espinosa, & Loza‐Rubio, ). Whether this represents species‐specific virulence motifs of IPNV, that is, Atlantic salmon versus rainbow trout, can only be speculated.…”
Section: Discussionsupporting
confidence: 86%
“…Moving on to Asia, Iranian Sp IPNV isolates obtained from cultured rainbow trout were demonstrated to have the Pro 217 -Thr 221 -Ala 247 profile [101] ( Figure 6K), which disagrees with Song et al [95]. In Mexico [102], IPNV isolates showed Thr at position 221 ( Figure 6L) which is indicative of persistence; however, although most isolates were from asymptomatic carriers-which confirms the predictions-one corresponded to an isolation from diseased rainbow trout. Something similar was reported in Chile [103], Turkey [104], and Taiwan [105], with isolates from clinical cases showing Thr at aa 221 .…”
Section: Determinants Of Virulence In Vp2mentioning
confidence: 71%
“…In Mexico, epidemiological studies identified IPNV by the principal national zones of production of rainbow trout [17,21], and in 2009 was reported a prevalence of 11.90% [21]. Genotyping and phylogenetic studies by VP2 gene from Mexican IPNV isolates have been performed [2,7,22], however its biological virulence is unknown. The objective of the present study was to determine the virulence of Mexican isolates in rainbow trout fry and related the results to VP2 amino acid fingerprint of the virus.…”
mentioning
confidence: 99%
“…From cell culture supernatant was extracted total RNA using TRIzol ® Reagent (Life Technologies, Carlsbad, CA, USA), according to manufacturer's protocol. Two sets of DNA oligonucleotide primers were designed to amplify the VP2 gene of the Sp strain, and of the Mexican isolates MEX3-CSM-05, MEX2-CSM-07 (GenBank accession numbers: AF342728.1, MH708133.1, MH708132.1, respectively) [22]. The oligonucleotide primers used were: INFE1+ 5′-ATGAGCACATCCAAGGCAA-3′ (position 137-160) and INFE1-5′-TCTGATGCCTCTGACTAGGTCC-3′ (position 796-818), with an amplified PCR product of 682 bp and INFE2+ 5′-ATTCGACCAGTGGCTAGAGACG-3′ (position 482-503) and INFE2-5′-GCGGTCTGCTGGTTGAGCTGG-3′ (position 688-710), with an amplified PCR product of 229 bp.…”
mentioning
confidence: 99%